Governance for sustainability: Towards a 'thick' understanding of environmental decision making - William Neil Andger; Katrina Brown; Jenny Fairbrass; Andrew Jordan; Jouni Paavola; Sergio Posendo (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2002)
Environmental decisions made by individuals, civil society and the state involve questions of economic efficiency, environmental effectiveness, equity and political legitimacy. These four criteria are constitutive of economic, social and environmental dimensions of sustainable development, which has become the dominant rhetorical device of environmental governance. We discuss the tendency for different strands of social science to focus on particular subsets of the four criteria and argue that such a practice promotes solutions that do not acknowledge the dynamics of scale and the heterogeneity of institutional and historical contexts. We propose a more interdisciplinary approach to understanding environmental decisions that seeks to identify legitimate and context-sensitive institutional solutions producing equitable, efficient and effective outcomes. We examine two examples that illustrate the indivisible and integrated nature of the four criteria in actual environmental decisions. The first example relates to international efforts to reduce greenhouse gas emissions and the second one to local resource management in the UK. We utilise the example to outline a new agenda for future research on environmental governance and decision-making.
Keywords: 330; contextuality; environmental decision-making; environmental governance; institutional arrangements; interdisciplinary research; Umweltforschung; Klimaschutz; Theorie; Interdisziplinäre Forschung